RETRACTED: Implementation of reversible jump MCMC algorithm to segment the piecewise Polynomial Regression - Suparman Suparman (Universitas Ahmad Dahlan, 2016)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in International Journal of Advances in Intelligent Informatics to article entitled “Implementation of reversible jump MCMC algorithm to segment the piecewise Polynomial Regression” Vol 2, No 2, pp. 88-93, July 2016, DOI: http://dx.doi.org/10.26555/ijain.v2i2.62.This paper has been found to be in violation of the International Journal of Advances in Intelligent Informatics Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in International Journal of Mathematical, Computational, Physical, Electrical and Computer Engineering, Vol. 10, No. 5 (2016), pp. 232-235, URL: http://scholar.waset.org/1999.7/10004307, entitled